ANSYS mechanical APDL for finite element analysis - Thompson, Mary Kathryn; Thompson, John M., (Mechanical engineer) (Butterworth-Heinemann, an imprint of Elsevier, 2017)
Provides a hands-on introduction to engineering analysis using one of the most powerful commercial general purposes finite element programs on the market. Students will find a practical and integrated approach that combines finite element theory with best practices for developing, verifying, validating and interpreting the results of finite element models, while engineering professionals will appreciate the deep insight presented on the program's structure and behavior. Additional topics covered include an introduction to commands, input files, batch processing, and other advanced features in ANSYS.